Evaluating for Human Herpesvirus 6 in the Liver Explants of Children With Liver Failure of Unknown Etiology. (10th November 2018) - Yang, Christine H; Sahoo, Malaya K; Fitzpatrick, Megan; Lau, Audrey H; Pinsky, Benjamin A; Martinez, Olivia M
Abstract: Background: Liver failure of unknown etiology (LFUE) has a transplant-free survival rate <25%. Human herpesvirus 6 (HHV-6) may be associated with LFUE, but studies are limited by small sample size. Methods: We identified all children who underwent liver transplant for LFUE at a single quaternary children's hospital; 51/65 cases could be age matched with controls (children who underwent liver transplant for metabolic liver disease). Quantitative polymerase chain reaction for HHV-6 was performed on DNA from formalin-fixed paraffin-embedded liver explant tissue. Results: HHV-6 was detected in 34/51 cases (66.7%) and 19/51 controls (37.3%) ( P = .005). Average HHV-6 viral load was 213207 copies/10 6 cells in positive cases (range: 7293–1102030) and 38115 copies/10 6 cells in positive controls (range: 1382–122375) ( P = .0008). HHV-6 was present significantly more often in cases compared to controls in patients younger than 6 years. In particular, in patients younger than 3 years, HHV-6 was present in 13/27 cases (48.1%) and 2/27 controls (7.4%) ( P = .0009). Conclusions: HHV-6 was detected in liver explants significantly more often and in higher quantities in children transplanted for LFUE compared to controls, suggesting HHV-6 should be evaluated in young children who present with LFUE. Abstract : Human herpesvirus 6 was found significantly more often and in higher quantities in the liver explants of children transplanted for liver failure of unknown etiology compared to age-matched controls, which were liver explants of children transplanted for metabolic liver disease.